Implementation of free maternal and child healthcare policies: assessment of influence of context and institutional capacity of health facilities in South-east Nigeria - Daniel C. Ogbuabor; Obinna E. Onwujekwe (Taylor & Francis Group, 2018)
Background: Studies examining how the capacity of health facilities affect implementation of free healthcare policies in low and middle-income countries are limited. Objective: This study describes how the context and institutional capacity of health facilities influenced implementation of the free maternal and child health programme (FMCHP) in Enugu state, South-east Nigeria. Methods: We conducted a qualitative case study at the state level and in two health districts (Isi-Uzo and Enugu Metropolis) in Enugu State. Data were collected through document review and semi-structured, in-depth interviews with policymakers (n = 16), healthcare providers (n = 16) and health facility committee leaders (n = 12) guided by an existing capacity framework and analysed using a thematic framework approach. Results: The findings reveal that active health facility committees, changes in provider payment process, supportive supervision, drug revolving fund, availability of medical equipment, electronic data transmission and staff sanction system enhanced the capacity of health facilities to offer free healthcare. However, ineffective decentralisation, irregular supervision and weak citizen participation limited this capacity. Uncertain provider payment, evidence of tax payment policy and a co-existing fee-exempt scheme constrained health facilities in following the FMCHP guidelines. Poor recording and reporting skills and lack of support from district officials constrained providers' adherence to claims' submission timeline. Poor funding, weak drug supply system, inadequate infrastructure and lack of participatory decision-making constrained delivery of free healthcare. Insufficient trained workforce, mission-inconsistent postings and transfers, and weak staff disciplinary system limited the human resource capacity. Conclusions: Effectiveness of FMCHP at the health facility level depends on the extent of decentralisation, citizen participation, concurrent and conflictive policies, timely payment of providers, organisation of service delivery and human resources practices. Attention to these contextual and institutional factors will enhance responsiveness of health facilities, sustainability of free healthcare policies and progress towards universal health coverage.